The Effect of Kinesio Taping on the Reduction of Pain in Patients with Carpal Tunnel Syndrome: Meta-Analysis - Setiawan, Cahyo; Tamtomo, Didik Gunawan; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Carpal tunnel syndrome (CTS) is the most common occurrence of nerve compression. Some cases of CTS have chronic symptoms. The most common complaint is